2021
DOI: 10.3389/fphar.2021.734774
|View full text |Cite
|
Sign up to set email alerts
|

The Novel Antioxidant Compound JSH-23 Prevents Osteolysis by Scavenging ROS During Both Osteoclastogenesis and Osteoblastogenesis

Abstract: Inflammatory osteolysis is a pathological skeletal disease associated with not only the production of inflammatory cytokines but also local oxidative status. Excessive reactive oxygen species (ROS) promote bone resorption by osteoclasts and induce the apoptosis of osteoblasts. In consideration of the lack of effective preventive or treatments options against osteolysis, the exploitation of novel pharmacological compounds/agents is critically required. In our study, we found that a novel antioxidant compound, J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Interestingly, pharmacological downregulation of ROS leads to reduced numbers of mature osteoclasts as well as decreased resorbing activity in the remaining OC via RANKL/NFATc1 signaling without cytotoxicity ( 29 , 50 , 51 ). As the intracellular ROS level is reduced by exposure to low doses of X-rays ( 52 ), this reduced level of oxidative stress could be one cause for the reduced resorbing activity of irradiated OC precursors in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, pharmacological downregulation of ROS leads to reduced numbers of mature osteoclasts as well as decreased resorbing activity in the remaining OC via RANKL/NFATc1 signaling without cytotoxicity ( 29 , 50 , 51 ). As the intracellular ROS level is reduced by exposure to low doses of X-rays ( 52 ), this reduced level of oxidative stress could be one cause for the reduced resorbing activity of irradiated OC precursors in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The ROS level in the distal femurs was assessed by DHE fluorescence, as previously described . In a nutshell, the samples received 4 weeks of fixation in 4% PFA, then were subjected to a gentle decalcification in solutions containing 10% EDTA.…”
Section: Methodsmentioning
confidence: 99%
“…The ROS level in the distal femurs was assessed by DHE fluorescence, as previously described. 7 In a nutshell, the samples received 4 weeks of fixation in 4% PFA, then were subjected to a gentle decalcification in solutions containing 10% EDTA. After that, the decalcified bones were submerged for 3 days in a solution consisting of 20% sucrose and 2% poly(vinylpyrrolidone).…”
Section: Ros Level In the Distalmentioning
confidence: 99%
See 1 more Smart Citation
“…9 HO-1 induction through transient gene vectors or bioactive small molecules impedes osteoclastogenesis. 10 In contrast, previous research has demonstrated that the suppression of HO-1 using RNA interference facilitates the development of osteoclasts. 11 The results of this study indicate that the activation of HO-1 expression by some drugs may confer a protective effect against pathological conditions characterized by the deterioration of bone tissue.…”
mentioning
confidence: 92%